Relationship between histone demethylase LSD family and development and prognosis of gastric cancer - Dong, Liyan; Zhu, Jiaxing; Deng, Anyi; Wei, Junping; Li, Jiawei; Mao, Xinru; Jia, Zhenghu (Frontiers in Immunology, 2023)
Objective to elucidate the correlation between histone demethylase and gastric cancer Research object histone demethylase and gastric cancer Results As one of the important regulatory mechanisms in molecular biology and epigenetics, histone modification plays an important role in gastric cancer including downstream gene expression regulation and epigenetics effect. Both histone methyltransferase and histone demethylases are involved in the formation and maintaining different of histone methylation status, which in turn through a variety of vital molecules and signaling pathways involved in the recognition of histone methylation modification caused by the downstream biological process, eventually participate in the regulation of chromatin function, and with a variety of important physiological activities, especially closely related to the occurrence of gastric cancer and embryonic development. Conclusion This paper intends to review the research progress in this field from the aspects of histone methylation modification and the protein structure, catalytic mechanism and biological function of the important histone demethylases LSD1 and LSD2, in order to provide the theoretical reference for further understanding and exploration of histone demethylases in development and prognosis of gastric cancer.